2020
DOI: 10.1108/ijotb-05-2019-0066
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organizational justice dimensions on facets of job engagement

Abstract: PurposeThis study aims to examine the relationship between four dimensions of organizational justice (distributive, procedural, interpersonal and informational) and the three facets of job engagement (physical, cognitive and emotional).Design/methodology/approachA cross-sectional approach was used to survey a sample of 281 professionals in information technology who resided in the southern part of India and varied on experience, age and gender. Data was analyzed by employing the partial least squares structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 101 publications
(133 reference statements)
3
9
0
Order By: Relevance
“…Organizational justice has a positive and significant effect on work engagement. The result supports the previous studies (Alvi & Abbasi, 2012;Storm et al, 2014;Lyu, 2016;Srimulyani, 2016;Özer et al, 2017;Hadiyani et al, 2018;Septiani & Arwiyah, 2018;Ivani et al, 2019;Ohiorenoya & Eguavoen, 2019;Deepa, 2020). The finding indicates that teachers are valuable to the organization, they are respected, and they are treated fairly, in turn work engagement of teachers increases.…”
Section: Relationship Between Organizational Justice and Work Engagementsupporting
confidence: 90%
“…Organizational justice has a positive and significant effect on work engagement. The result supports the previous studies (Alvi & Abbasi, 2012;Storm et al, 2014;Lyu, 2016;Srimulyani, 2016;Özer et al, 2017;Hadiyani et al, 2018;Septiani & Arwiyah, 2018;Ivani et al, 2019;Ohiorenoya & Eguavoen, 2019;Deepa, 2020). The finding indicates that teachers are valuable to the organization, they are respected, and they are treated fairly, in turn work engagement of teachers increases.…”
Section: Relationship Between Organizational Justice and Work Engagementsupporting
confidence: 90%
“…Hence, we can see here that "engagement" comprises emotional, cognitive, and behavioural components, meaning that engaged employees are naturally invested in organisations through their body, mind, and soul. However, the majority of the existing literature has addressed job engagement as one block, rather than in its three dimensions (Deepa, 2020). Notably, physical engagement refers to the physical aspect of job engagement (i.e., the physical energies exerted by employees to fulfil their tasks) (Kular, Gatenby, Rees, Soane, & Truss, 2008); or, in the other words, it concerns the willingness of the employees to make extra efforts for the employer.…”
Section: Job Engagementmentioning
confidence: 99%
“…Deepa (2020) found this to be the case when further exploring these issues in a survey of professionals employed in the IT sector in southern India. Responses from the self-reported questionnaire confirmed that all forms of organizational justice positively relate to each JE dimension.…”
Section: Indian Studymentioning
confidence: 90%